Response of Soybean Grown on a Claypan Soil in Southeastern Kansas to the Residual of Different Plant Nutrient Sources and Tillage - D. W. Sweeney; P. Barnes; G. Pierzynski (Kansas Agricultural Experiment Station Research Reports, 2015)
The residual effects of turkey litter and fertilizer amendments applied in previous years had little effect on the yield, yield components, and dry matter production of the following soybean crop grown in 2014.
Keywords: turkey litter; fertilizer; tillage; soybean; claypan